The Obligation of Notary as a Reporter in Efforts to Prevent and Eradicate Money Laundering Crime - Erwin Kunta Tejakusuma; Dwi Endah Nurhayati; Samuel Saut Martua Samosir (Faculty of Law, University of Jember, Indonesia, 2024)
Money laundering is a structured and diverse crime, the implementation of which can utilize financial institutions and institutions outside the financial system. In Government Regulation No. 43/2015 on Reporting Parties in the Prevention and Eradication of ML, it is stated that notary is one of the reporting parties. However, this obligation to report conflicts with the obligation to keep the contents of the deed and all information regarding the deed confidential as stipulated in the Notary Position Law. Notaries in carrying out their duties are bound by an oath of office that they must uphold. One of the notary oaths is regarding notary confidentiality as written in Article 4 Paragraph (2) of Law Number 30 Year 2004. In addition, notaries in carrying out their positions, based on Article 16 of UUJN Paragraph (1) letter f, notaries are obliged to